2016
DOI: 10.1186/s13256-016-0949-9
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid-type fibromatosis of the head and neck in children: a case report and review of the literature

Abstract: BackgroundDesmoid-type fibromatosis is defined as an intermediate tumor that rarely occurs in the head and neck of children. There is no doubt as to the value of complete surgical excision for desmoid-type fibromatosis. However, in pediatric patients, surgeons may often be concerned about making a wide excision because of the potential for functional morbidity. Some studies have reported a lack of correlation between margin status and recurrence. Therefore, we discussed our findings with a focus on the state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…1,2 These lesions typically occur in a bimodal distribution in infants and young adults without a gender predilection. 3,4 The etiology of DF is unknown, but trauma and hormonal influences have often been cited as possible causative factors. 4 The DF has also been associated with hereditary genetic syndromes such as familial adenomatous polyposis and hereditary desmoid disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 These lesions typically occur in a bimodal distribution in infants and young adults without a gender predilection. 3,4 The etiology of DF is unknown, but trauma and hormonal influences have often been cited as possible causative factors. 4 The DF has also been associated with hereditary genetic syndromes such as familial adenomatous polyposis and hereditary desmoid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional treatment has been wide local excision with negative surgical margins to decrease recurrence. 1,2,3,[9][10][11] Meazza et al reported a 22% versus 76% recurrence rate with DF with negative compared to positive surgical margins. 10 This has led to the use of adjuvant chemotherapy when positive margins are reported or recurrences occur, for tumor stabilization and regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] It is defined as an intermediate tumor that rarely occurs in the head and neck of children. [ 4 ] Lesions in the head and neck are reported in 12% of all cases, and 71% occur in the first decade of life. [ 2 , 5 ] There has been challenge to the management of fibromatosis in these pivotal anatomic areas because complete excision with a negative margin is usually impossible, and thus frequent local recurrence is common in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…When recurrence rates were compared in patients with grossly negative surgical margins and grossly positive surgical margins for head, neck, and spine DTs, two studies showed statistical significance (p < 0.05) for lower recurrence rate after gross total resection, and seven showed a trend toward lower recurrence rates in patients with gross total resection. A summary of the recurrence rates following grossly complete resections compared to grossly incomplete excisions in case series with DTs of the head and neck is presented [3,[22][23][24][25][26][27][28][29][30] (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%